Quadratic stochastic operators with countable state space - Ganikhodjaev, Nasir (Institute of Physics Publishing, 2016)
In this paper, we provide the classes of Poisson and Geometric quadratic stochastic operators with countable state space, study the dynamics of these operators and discuss their application to economics.